2016
DOI: 10.5114/pg.2016.61487
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Helicobacter pylori infection

Abstract: Helicobacter pylori infection has accompanied man for thousands of years. In some infected patients, a complex and dynamic pathogen-host reaction triggers pathogenic pathways resulting in development, inter alia, of atrophic gastritis, peptic ulcer disease (both gastric and duodenal), gastric adenocarcinoma, and MALT lymphoma. Large-scale eradication therapy is associated with a rapid increase in antibiotic resistance, gut flora composition disturbances, and increased risk of development, inter alia, of paedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
2
16
0
2
Order By: Relevance
“…In univariate analysis H. pylori was associated with several habits related to increased salt intake (adding extra salt to food and the consumption of pickled and meat products), but not in multivariate analysis after including a large number of factors. High salt intake has been shown not only to facilitate the colonization of the gastric mucosa by H. pylori but also increase inflammation and accelerate carcinogenesis [17,31]. Beevers et al [32] reported a correlation between urinary sodium excretion and H. pylori infection rates in 2004 in the EUROGAST and INTERSALT study population from ten countries [32] In our study the association between H. pylori and lower fruit and vegetable intake remained strong in multivariate analysis.…”
Section: Discussionsupporting
confidence: 57%
“…In univariate analysis H. pylori was associated with several habits related to increased salt intake (adding extra salt to food and the consumption of pickled and meat products), but not in multivariate analysis after including a large number of factors. High salt intake has been shown not only to facilitate the colonization of the gastric mucosa by H. pylori but also increase inflammation and accelerate carcinogenesis [17,31]. Beevers et al [32] reported a correlation between urinary sodium excretion and H. pylori infection rates in 2004 in the EUROGAST and INTERSALT study population from ten countries [32] In our study the association between H. pylori and lower fruit and vegetable intake remained strong in multivariate analysis.…”
Section: Discussionsupporting
confidence: 57%
“…More randomized controlled trials should be conducted to explore further the effect of different food components on H. pylori eradication. Such research would identify healthier alternatives for treating H. pylori colonization than pharmacological therapy that has side effects and leads to antibiotic resistance [ 51 ]. On the other hand, Xia et al argue that it is important to study dietary patterns and not food items in isolation, since nutrients do not only act independently but may also interact together [52] since H. pylori was positively association with a diet rich in carbohydrates and sweets, and negatively associated with a diet high in protein and cholesterol, while no association was found between H. pylori and any food items or groups studied in isolation in their cross sectional study.…”
Section: Discussionmentioning
confidence: 99%
“…Documented data revealed that 20% to 90% of hospitalized patients with gastrointestinal disorders were infected with H. pylori strains (5,6). In keeping with this, there were no previously recorded data regarding the main sources and also route of transmission of H. pylori into human (7). Several previously published data revealed that H. pylori had a significant prevalence in various types of foods, especially milk, meat, salad, vegetables, and ready to eat foods, which may show the food-borne route of this bacterium (8)(9)(10).…”
Section: Introductionmentioning
confidence: 90%